PENGARUH PENERAPAN MODEL KREATIF PRODUKTIF DAN KREATIVITAS BELAJAR TERHADAP KETERAMPILAN/KEMAMPUAN MENULIS PUISI SISWA - Patimah, Patimah; Sudaryono, Sudaryono; Rachmawati, Rachmawati (Program Magister Teknologi Pendidikan Universitas Jambi, 2012)
Effect of Application of Creative Learning Model Against Productive Learning and Creativity Skills / Ability Poetry Writing Students. The independent variable in this study is a model of PFM. Moderator variables were studied creativity. The instrument used to measure the skills / ability to write poems that use the test, to measure creativity while learning to use a questionnaire adapted from FLS2N national assessment guidelines in 2010. This study is an experimental study with a 2 X 2 factorial design with pretest and posttes. The data were analyzed using ANOVA analysis of two lanes and Tukey Test. The data were analyzed first before the proposed test ANOVA assumptions which includes test data normality and homogeneity test data. The results showed that: (1) there is a model of the influence of PKP and creativity to learn the skills / ability to write poetry, (2) there is an influence on creativity learning skills / ability to write poetry, (3) there is the effect of using PFM model of the skill / ability to write poetry students who have studied high creativity, (4) there is an influence of the PFM modeling skills / ability to write poetry students who have studied creativity is low, and (5) there is no interaction between PKP and creativity models learn the skills / abilities of students to write poetry. Keyword: Productive Creative Learning, Creative Learning, Skills / capabilities Writing Poetry